Renin-Angiotensin System Blockers May Prolong Survival of Metastatic Non-Small Cell Lung Cancer Patients Receiving Erlotinib. Issue 22 (June 2015) - Aydiner, Adnan; Ciftci, Rumeysa; Sen, Fatma
Abstract : Abstract: The aim of this study is to determine whether renin-angiotensin system blockers (RASBs), which include angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin-2 receptor 1 blockers (ARBs), improve the overall survival (OS) of patients with metastatic non-small cell lung cancer (NSCLC). The medical charts of 117 patients with metastatic NSCLC were retrospectively assessed. Thirty-seven patients (RASB group) using RASBs during systemic treatment were compared with 80 controls (control group) who did not use RASBs following the diagnosis of NSCLC. The histological tumor subtype, performance status, age, sex, smoking status, comorbidities, other medications, chemotherapeutics (CT), and erlotinib that were received in any line of treatment were recorded. We compared the OS of the patients in the RASB and control groups. The median (±SD) age of the patients was 61 (±1) years and all patients were administered systemic treatment (CT or erlotinib). The patients in RASB group were more likely to be smokers, have hypertension and ischemic heart disease, and use erlotinib, thiazides, beta-blockers, and calcium-channel blockers ( P < 0.05 for all) compared with the control group. The median follow-up time was 18.9 months (range 1–102 months) for the entire group. The median follow-up period was longer for RASB group than control group (17 vs 11 months, P = 0.033). The most commonly prescribed RASB agent was valsartan (n = 12/37). At the time of the analysis, 98 (83.7%) of all patients had died. In the univariate analysis, the median OS was longer in the RASB group compared with the control group (17 [±4.1] vs 12 [±1.4] months, P = 0.016). Interestingly, further analyses revealed that RASBs significantly improved OS only if used with erlotinib concurrently (34 [±13.8] vs 25 [±5] months, P = 0.002) and the OS benefit was more attributable to ARBs because only 4 patients received ACEI and erlotinib concurrently. However, the benefit of ARBs on OS disappeared in the multivariate analysis. The use of ARBs during erlotinib treatment may prolong OS of patients with metastatic NSCLC.